Antibacterial Activity Test of Basil Leaves (Ocimum basilicum L.) Against Staphylococcus aureus Using the Diffusion Agar Method - Selvana S. Tulandi; Joke L. Tombuku (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2025)
Infections caused by Staphylococcus aureus are among the leading causes of morbidity and mortality worldwide, particularly due to the increasing resistance to antibiotics. This study aims to evaluate the antibacterial activity of basil leaves (Ocimum basilicum L.) against S. aureus using the agar diffusion method. This laboratory experimental study used a completely randomized design: extract concentration treatments (100µL, 200µL, 300µL, 400µL), a positive control (synthetic antibiotic @amoxicillin), and a negative control (distilled water), each with three replications. The data were analyzed using non-parametric statistics, as the data were not normally distributed and lacked homogeneity. The Kruskal-Wallis ANOVA was used to determine differences between treatments. The results showed that basil leaf extract exhibited significant antibacterial activity, with all concentrations inhibiting the growth of S. aureus. The highest inhibition zone was observed at the 400µL concentration, with an average diameter of 9.28 ± 0.36 mm. These findings suggest the potential of basil leaves as a natural antibacterial source for developing alternative therapies against S. aureus infections.